Observation of strong magneto plasmonic nonlinearity in bilayer graphene discs. (15th January 2021) - Chin, Matthew L; Matschy, Sebastian; Stawitzki, Florian; Poojali, Jayaprakash; Hafez, Hassan A; Turchinovich, Dmitry; Winnerl, Stephan; Kumar, Gagan; Myers-Ward, Rachael L; Dejarld, Matthew T; Daniels, Kevin M; Drew, H Dennis; et al.
Abstract: Graphene patterned into plasmonic structures like ribbons or discs strongly increases the linear and nonlinear optical interaction at resonance. The nonlinear optical response is governed by hot carriers, leading to a red-shift of the plasmon frequency. In magnetic fields, the plasmon hybridizes with the cyclotron resonance, resulting in a splitting of the plasmonic absorption into two branches. Here we present how this splitting can be exploited to tune the nonlinear optical response of graphene discs. In the absence of a magnetic field, a strong pump-induced increase in on-resonant transmission can be observed, but fields in the range of 3 T can change the characteristics completely, leading to an inverted nonlinearity. A two temperature model is provided that describes the observed behavior well.